Synthesis of New Reconfigurable Limited Size FSS Structures Using an Improved Hybrid Particle Swarm Optimization - Lacouth,Patric (2019)
Abstract This paper describes a new design methodology for reconfigurable printed circuits with limited size, using an improved hybrid particle swarm optimization (HPSO) algorithm, reducing the search space by the definition of negative zones (NZ), regions where the swarm of particles should not travel. The proposed design methodology (HPSO-NZ) is used in the development of reconfigurable frequency selective surfaces (RFSSs), restricted to a limited overall size, resulting in entirely new frequency selective surface (FSS) geometries. Two FSS prototypes are designed, fabricated, and measured for comparison purpose. A good agreement is observed between simulation and measurements results, confirming the efficiency and accuracy of the HPSO-NZ algorithm. Also, the performance of the HPSO-NZ algorithm is compared to the ones of genetic algorithm (GA) and particle swarm optimization (PSO) algorithm, showing good consistency results.